Procatalyst for promoting Fe < 3 + > reduction in electro-Fenton application process and preparation method thereof

By preparing a porous nanospherical cocatalyst, the thermal cracking reaction of sodium molybdate and thiourea and the porous structure of fine slag gasified by coal, the problem of low Fe3+ reduction efficiency in electrofenton technology was solved, and efficient and economical organic wastewater treatment effect was achieved.

CN119565639AActive Publication Date: 2025-03-07SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411744014.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-03-07
Estimated Expiration
2044-11-30

AI Technical Summary

Technical Problem

The low reduction efficiency of Fe3+ in the existing electrofenton technology leads to high ferrous recycling and regeneration costs and is prone to secondary pollution, which limits the processing efficiency and application promotion of this technology.

Method used

A porous nanospherical cocatalyst is prepared by materials such as sodium molybdate, thiourea and coal gasified fine slag. The nanosheet-like molybdate is reacted with thiourea to form a cluster of molybdate sulfide, and is loaded in the pores of coal gasified fine slag through microwave drying and freeze-drying technology to form a solid solution.

Benefits of technology

The reduction efficiency of Fe3+ is significantly improved, the generation of strong oxidative free radicals by the Fenton reaction is enhanced, and the treatment effect of organic wastewater is significantly improved. The cocatalyst is effective under acidic, neutral and alkaline conditions, reducing secondary pollution and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565639A_ABST
    Figure CN119565639A_ABST
Patent Text Reader

Abstract

The invention provides a cocatalyst for promoting Fe < 3 + > reduction in the electro-Fenton application process and a preparation method thereof, and relates to the field of wastewater treatment.The preparation method comprises the steps that sodium molybdate, thiourea and coal gasification fine slag are evenly dispersed in deionized water, the mass ratio of sodium molybdate to thiourea is (0.30-2.5): (1.5-3.5), and a mixed system is obtained; the mixed system is subjected to heat preservation treatment at the temperature of 120-180 DEG C, sodium molybdate is subjected to a reduction reaction with thiourea after being subjected to thermal decomposition, nano lamellar cluster-shaped molybdenum sulfide is obtained, and reaction liquid is obtained; sediments in a reaction solution are subjected to microwave drying and freeze drying to obtain the cocatalyst for promoting Fe < 3 + > reduction in the electro-Fenton application process, Fe < 3 + > reduction can be promoted through valence change of molybdenum ions dissolved out of a solution and the unsaturated property of sulfur, and therefore Fenton reaction is enhanced to generate strong oxidizing free radicals to treat organic wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of wastewater treatment, and in particular to a method for promoting Fe 3+ A reduced promoter and a method for preparing the same. Background Art

[0002] Electro-Fenton technology (EF) is a new type of electrochemical advanced oxidation technology based on Fenton chemical reaction that has been developed in water treatment technology in recent years. EF is driven by electrical energy and produces H2O2 in situ through the cathode oxygen reduction reaction (ORR), which then induces the production of OH. It has the advantages of high oxidation efficiency, greenness, and controllability, and has become a new technology for efficient treatment of difficult-to-degrade organic pollutants. EF is driven by electrical energy. The basic principle is that dissolved oxygen produces hydrogen peroxide (H2O2) on the surface of a suitable cathode material through a two-electron oxygen reduction reaction. The generated H2O2 can react with Fe in the solution. 2+ The catalyst reaction produces a strong oxidant hydroxyl radical (·OH), and the reaction formula is as follows:

[0003] H2O2+Fe 2+ →Fe 3+ +·OH+OHˉ

[0004] EF removes refractory organic matter by utilizing the non-selective strong oxidizing ability of ·OH. It has the advantages of high oxidation efficiency, greenness, and controllability, and has become one of the highly-regarded technologies for the efficient treatment of organic matter in water.

[0005] The divalent and trivalent cyclic reactions of iron ions play an important role in the production of OH. 3+ +eˉ→Fe 2+ .Fe 3+ Reduction to Fe 2+ However, in the actual reaction, most EF cathodes have hydrophobic interface characteristics, which is not conducive to Fe 2+ Recycling, Fe 3+ The reduction rate is low and the treatment system is limited to the pH range (2-3), which are the main factors limiting the treatment efficiency and application promotion of this technology.

[0006] At present, the methods for enhancing the recycling of ferrous iron in the electro-Fenton system mainly include adding reducing substances (chelate ligands), heterogeneous metal materials (the Fenton reaction rate is slow and difficult to recycle) and ultraviolet radiation. However, the above methods are costly and easy to cause secondary pollution, and Fe 3+ The low reduction efficiency results in no significant improvement in the treatment effect of this technology. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention provides a method for promoting Fe 3+ The reduced catalyst and its preparation method solve the problems of high cost, secondary pollution and Fe 3+ The problem of low reduction efficiency effectively promoted the Fe 3+ circulation and the Fenton reaction.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] A method to promote Fe 3+ The preparation method of the reduced promoter comprises the following steps:

[0010] S1, uniformly dispersing sodium molybdate, thiourea and coal gasification fine slag in deionized water, wherein the mass ratio of sodium molybdate to thiourea is (0.30-2.5):(1.5-3.5), to obtain a mixed system;

[0011] S2, heat-insulating the mixed system at 120-180° C., thermally decomposing sodium molybdate and reacting with thiourea to obtain nanosheet-like clusters of molybdenum sulfide, and obtaining a reaction solution;

[0012] S3, the sediment in the reaction solution is dried by microwave, and then freeze-dried to obtain Fe 3+ Reduction promoter.

[0013] A further improvement of the present invention is:

[0014] The mass ratio of sodium molybdate to coal gasification fine slag in S1 is (0.30-2.5):(0.5-4).

[0015] S1: Sodium molybdate and coal gasification fine slag are first dispersed uniformly in deionized water to obtain a mixed system a, and then thiourea, citric acid aqueous solution and isopropanol are added and mixed uniformly to obtain a mixed system.

[0016] S2: heat the mixed system at 120-180°C for 4-8 hours to obtain a reaction solution.

[0017] S2 first centrifuges the reaction solution, then removes the supernatant, and finally microwaves dry at 500-1500W.

[0018] The microwave drying is carried out under the condition of introducing N2 at a flow rate of 2-15 L / min.

[0019] The microwave drying is carried out at 60-120° C. for 20-40 min.

[0020] The power of S3 freeze drying is 500-1200W.

[0021] The freeze drying described in S3 is carried out at -20 to -10°C for 10 to 30 minutes.

[0022] A method for promoting Fe in the electro-Fenton application process according to any one of the above 3+ Preparation method of reduced co-catalyst obtained to promote Fe in electro-Fenton application process 3+ The reduced catalyst is a porous nano-spherical structure with a specific surface area of ​​1200-2500 g / cm 2 , porosity is 65%-85%, pore volume is 0.12-0.30g / cm 3 .

[0023] Compared with the prior art, the present invention has at least the following beneficial effects:

[0024] The invention discloses a method for promoting Fe 3+ The invention discloses a preparation method of a reducing co-catalyst. Sodium molybdate is thermally decomposed at 120-180°C and then reacted with thiourea to undergo a reduction reaction to obtain nano-sheet clustered molybdenum sulfide. There are channels between the sheets. Different temperatures can adjust the particle size of the molybdenum sulfide and the interlayer spacing of the sheets. Too high a temperature will cause the collapse of the molybdenum sulfide sheet structure. The coal gasification slag is a porous structure. Through microwave radiation, the molybdenum sulfide can be loaded inside and outside the pores of the coal gasification fine slag to wrap the coal gasification fine slag to form a solid solution and a porous spherical structure. After that, a heterogeneous catalyst can be obtained by freeze drying. The valence state change of the molybdenum ions dissolved in the solution and the unsaturation of sulfur can promote Fe 3+ Reduction, thereby strengthening the Fenton reaction to produce strong oxidizing free radicals to treat organic wastewater. The electro-Fenton system containing the heterogeneous catalyst can have good treatment effects in acidic, neutral and alkaline wastewater. The present invention makes full use of the molybdenum sulfide formed by the thermal decomposition of sodium molybdate and thiourea to release molybdenum ions to promote the circulation of ferrous ions, and regulates the pH of the solution through unsaturated sulfur atoms to promote the Fenton reaction. The present invention uses the solid waste gasification slag after coal gasification heating, on the one hand, uses its high specific surface area and porous structure to load the molybdenum sulfide co-catalyst and regulate the surface morphology, and on the other hand, it uses coal-based solid waste to achieve high-value utilization, reduces the amount of solid waste stockpiling and realizes its resource processing. The present invention can use simple equipment to prepare the co-catalyst, is easy to operate, and can be promoted and applied industrially, making EF a good treatment effect, economical and efficient, and environmentally friendly organic wastewater treatment method, which has important theoretical and practical significance for promoting the industrial application of electro-Fenton technology.

[0025] The catalyst obtained by the present invention is a porous nano-spherical structure with a specific surface area of ​​1200-2500 g / cm 2, porosity is 65%-85%, pore volume is 0.12-0.30g / cm 3 , can be used in EF system, can effectively improve the EF treatment effect, and can effectively remove pollutants under acidic, neutral and alkaline conditions. The co-catalyst can effectively improve the reduction efficiency of ferric iron to ferrous iron in the EF system. Before and after the use of the co-catalyst, the surface structure of the material is stable, which is conducive to repeated use. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is an electron microscope scanning image of the surface of the co-catalyst material prepared in Example 1 of the present invention.

[0027] Figure 2 This is a diagram showing the efficiency of treating organic wastewater using the co-catalyst prepared in Example 1 of the present invention and the system EF without co-catalyst.

[0028] Figure 3 This is a cycle diagram of iron ion concentration of the co-catalyst system and the system without co-catalyst prepared in Example 2 of the present invention.

[0029] Figure 4 This is a comparison chart of the treatment rates of organic wastewater by the co-catalyst prepared in Example 2 of the present invention under different pH conditions.

[0030] Figure 5 This is the X-ray diffraction analysis diagram of the catalyst wastewater prepared in Example 3 of the present invention before and after treatment. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments, which are intended to explain the present invention rather than to limit it.

[0032] The invention discloses a method for promoting Fe 3+ The preparation method of the reduced promoter is specifically implemented according to the following steps:

[0033] Step 1: Weigh 0.30-2.5 g of sodium molybdate and 0.5-4 g of coal gasification fine slag, and ultrasonically disperse the two in 50-100 mL of deionized water to obtain a mixed system;

[0034] Step 2: Weigh 1.5-3.5 g of thiourea, a total volume of 4-10 ml of citric acid aqueous solution and isopropanol, add them to the mixed system in step 1, and stir for 10-20 minutes, wherein the volume ratio of the citric acid aqueous solution to the isopropanol is 30%:70%, and the mass fraction of the citric acid aqueous solution is 60%;

[0035] Step 3: transfer the mixed system obtained in step 2 into a high pressure reactor, set the temperature to 120-180°C, and the reaction time to 4-8 hours;

[0036] Step 4: Place the reaction solution after step 3 into a centrifuge, set the centrifugal speed to 2000-5000 rpm / min, and the centrifugal time to 5-10 minutes;

[0037] Step 5: remove the supernatant, put the sediment into a microwave drying oven with a power of 500-1500 W, introduce N2 at a flow rate of 2-15 L / min, set the temperature to 60-120° C., and dry for 20-40 minutes, then quickly put it into a freeze drying oven with a power of 500-1200 W, a drying temperature of -20 to -10° C., and a drying time of 10-30 min to obtain the nano-spherical co-catalyst material prepared by the present invention.

[0038] The coal gasification slag is the solid waste discharged after high-temperature gasification in the coal gasification furnace of a thermal power plant in Yulin, Shaanxi. The specific surface area of ​​the catalyst material is 1200-2500g / cm 2 , porosity is 65%-85%, pore volume is 0.12-0.30g / cm 3 .

[0039] The present invention also provides a method for effectively treating organic wastewater, using common carbon-based materials currently on the market as cathodes (carbon felt, activated carbon fibers, carbon cloth, graphite felt, etc.) (area 20-200 cm 2 ), using a commercially available metal-coated stable electrode as the anode (DSA) (area 20-200cm 2 ), adding catalyst ferrous sulfate (0.2-5mmol) and the promoter prepared by the present invention (2-25mg), 50-1000mL of organic wastewater, after electro-Fenton treatment, the removal rate of organic pollutants can reach 85-98% within 10-30min, and can be well removed at pH values ​​of 3, 4, 5, 7 and 9. At the same time, since the iron and mineral components of the coal gasification slag are magnetic, the promoter is recyclable, which improves the effect of the electro-Fenton water treatment technology and has important practical significance for the industrial application and promotion of the electro-Fenton technology.

[0040] Example 1

[0041] Step 1: Weigh 0.35 g of sodium molybdate and 1.0 g of coal gasification fine slag, and ultrasonically disperse them in 55 mL of deionized water;

[0042] Step 2: Weigh 1.5 g of thiourea and slowly add it to the mixed system obtained in step 1, and stir for 10 minutes;

[0043] Step 3: Take 4 ml of citric acid aqueous solution and isopropanol and add them to the mixed system obtained in step 2, wherein the volume ratio of citric acid aqueous solution to isopropanol is 30%:70%, and the mass fraction of citric acid aqueous solution is 60%;

[0044] Step 4: Place the mixed system obtained in the above step into a high pressure reactor, set the temperature to 120°C, and the reaction time to 4 hours;

[0045] Step 5: Transfer the reaction solution after the reaction in step 4 to a centrifuge, set the centrifugal speed to 2000 rpm / min, and the centrifugal time to 5 minutes;

[0046] Step 6: remove the supernatant, put the sediment into a microwave drying oven with a power of 1000w, introduce N2, a flow rate of 4L / min, a set temperature of 80°C, and a drying time of 20 minutes, and then quickly put it into a freeze drying oven with a power of 1000w, a drying temperature of -10°C, and a drying time of 10 minutes to obtain the co-catalyst material prepared by the present invention.

[0047] The surface morphology of the catalyst Figure 1 As shown, it is a porous nano-spherical structure that can regulate the dissolution of metal ions and effectively carry out catalytic reactions. The specific surface area of ​​the co-catalyst material is 1200g / cm 2 , porosity is 65%, pore volume is 0.15g / cm 3 .

[0048] The co-catalyst prepared by the present invention can improve the Fenton reaction treatment effect on phenol-containing organic wastewater discharged from a chemical plant. Figure 2 As shown in the figure, the COD removal rate of the catalyst system can reach 100% within 30 minutes, while that of the system without catalyst is 33%. 2 ), with a metal-coated stable electrode as the anode (40 cm 2 ), adding ferrous sulfate catalyst (0.4 mmol) and the co-catalyst prepared by the present invention (10 mg). After the treatment by the present invention, the COD removal rate can reach 85% within 30 minutes, which is 2.5 times that of the system without adding the co-catalyst.

[0049] The co-catalyst prepared by the present invention can effectively increase the Fe 2+ The co-catalyst prepared by the present invention can be used to quickly and efficiently treat organic wastewater under acidic, neutral and alkaline conditions. The co-catalyst prepared by the present invention can be recycled and reused multiple times.

[0050] Example 2

[0051] Step 1: Weigh 0.40 g of sodium molybdate and 0.80 g of coal gasification fine slag, and ultrasonically disperse them in 70 mL of deionized water;

[0052] Step 2: Weigh 2 g of thiourea and slowly add it to the mixed system obtained in step 1, and stir for 15 minutes;

[0053] Step 3: Take 5 ml of citric acid aqueous solution and isopropanol and add them to the mixed system obtained in step 2, wherein the volume ratio of citric acid aqueous solution to isopropanol is 30%:70%, and the mass fraction of citric acid aqueous solution is 60%;

[0054] Step 4: The mixed system obtained in the above step is transferred into a high pressure reactor, and the temperature is set to 120° C. for 5 hours;

[0055] Step 5: Place the reaction solution after step 4 into a centrifuge, set the centrifugal speed to 3000 rpm and the centrifugal time to 6 minutes.

[0056] Step 6: remove the supernatant, put the sediment solution into a microwave drying oven with a power of 1200 W, introduce N2, a flow rate of 5 L / min, a set temperature of 80°C, and a drying time of 25 minutes, and then quickly put it into a freeze drying oven with a power of 1000 W, a drying temperature of -12°C, and a drying time of 15 minutes to obtain the co-catalyst material prepared by the present invention.

[0057] The specific surface area of ​​the catalyst material is 1500 g / cm 2 , porosity is 72%, pore volume is 0.20g / cm 3 .

[0058] The co-catalyst prepared by the present invention can improve the treatment efficiency of organic wastewater by electro-Fenton technology. 2+ The cycle is generated. Figure 3 As shown, in the co-catalyst system, when the reaction time is 5 min, Fe 2+ The concentration began to rise, 20min Fe 2+ The concentration is equivalent to the added amount, but no co-catalyst system is added. 2+ The concentration continues to decrease and the iron recycling effect is poor.

[0059] The co-catalyst prepared by the present invention can effectively treat organic wastewater under acidic, neutral and alkaline conditions. Figure 4 As shown in the figure, the electro-Fenton treatment technology with the addition of the catalyst can achieve effective removal at pH 3, 4, 5, 7 and 9. Compared with the system without the addition of the catalyst, the COD removal effect and removal rate are greatly improved. The treatment rate (Kmin -1 ) can be increased up to 7-8 times.

[0060] The co-catalyst prepared by the present invention can be recovered and reused multiple times.

[0061] Example 3

[0062] Step 1: Weigh 1.5 g of sodium molybdate and 2.0 g of coal gasification fine slag, and ultrasonically disperse them in 85 mL of deionized water;

[0063] Step 2: Weigh 2.5 g of thiourea and slowly add it to the mixed system obtained in step 1, and stir for 18 minutes;

[0064] Step 3: Take 6 ml of citric acid aqueous solution and isopropanol and add them to the mixed system obtained in step 2, wherein the volume ratio of citric acid aqueous solution to isopropanol is 30%:70%, and the mass fraction of citric acid aqueous solution is 60%;

[0065] Step 4: The mixed system obtained in the above step is transferred into a high pressure reactor, and the temperature is set to 150° C. for 5.5 hours;

[0066] Step 5: Place the reaction solution after the reaction in step 4 into a centrifuge, set the centrifugal speed to 3800 rpm, and the centrifugal time to 8 minutes;

[0067] Step 6, remove the supernatant, put the sediment solution into a microwave drying oven with a power of 1300W, introduce N2, a flow rate of 6L / min, a set temperature of 85°C, and a drying time of 24 minutes, and then quickly put it into a freeze drying oven with a power of 1000W, a drying temperature of -15°C, and a drying time of 15 minutes to obtain the co-catalyst material prepared by the present invention.

[0068] The specific surface area of ​​the catalyst material prepared by the present invention is 1800 g / cm 2 , porosity is 72%, pore volume is 0.23g / cm 3 .

[0069] The co-catalyst prepared by the present invention can improve the Fenton reaction on the COD treatment effect of organic wastewater discharged from a chemical plant. 2+ The co-catalyst prepared by the present invention can quickly and efficiently treat organic wastewater under acidic, neutral and alkaline conditions. The co-catalyst prepared by the present invention can be recycled and reused many times. Figure 5 As shown, by performing X-ray scanning on the co-catalyst before use and after 20 consecutive operations, it was found that its elemental composition and structure were still stable, indicating that the co-catalyst prepared by the present invention has good organic wastewater treatment performance and can be reused many times. The co-catalyst prepared by the present invention saves raw materials and is suitable for industrial promotion and application.

[0070] In summary, the method for preparing the co-catalyst of the present invention is simple and convenient, and Fe 3+ It has high reduction efficiency, expands the pH application range of EF technology, and can treat organic wastewater efficiently and stably.

Claims

1. A method to promote Fe 3+ A method for preparing a reduced promoter, characterized in that: The following steps are involved: S1, uniformly dispersing sodium molybdate, thiourea and coal gasification fine slag in deionized water, wherein the mass ratio of sodium molybdate to thiourea is (0.30-2.5):(1.5-3.5), to obtain a mixed system; S2, heat-insulating the mixed system at 120-180° C. to obtain a reaction solution; S3, the sediment in the reaction solution is dried by microwave, and then freeze-dried to obtain Fe 3+ Reduction promoter.

2. The Fe-promoting electro-Fenton application process according to claim 1 3+ A method for preparing a reduced promoter, characterized in that: The mass ratio of sodium molybdate to coal gasification fine slag in S1 is (0.30-2.5):(0.5-4).

3. The Fe in the process of promoting electro-Fenton application according to claim 1 3+ A method for preparing a reduced promoter, characterized in that: S1: Sodium molybdate and coal gasification fine slag are first dispersed uniformly in deionized water to obtain a mixed system a, and then thiourea, citric acid aqueous solution and isopropanol are added and mixed uniformly to obtain a mixed system.

4. The Fe-promoting electro-Fenton application process according to claim 1 3+ A method for preparing a reduced promoter, characterized in that: S2: heat the mixed system at 120-180°C for 4-8 hours to obtain a reaction solution.

5. The Fe-promoting electro-Fenton application process according to claim 1 3+ A method for preparing a reduced promoter, characterized in that: S2 first centrifuges the reaction solution, then removes the supernatant, and finally microwaves dry at 500-1500W.

6. The Fe-promoting electro-Fenton application process according to claim 5 3+ A method for preparing a reduced promoter, characterized in that: The microwave drying is carried out under the condition of introducing N2 at a flow rate of 2-15 L / min.

7. The Fe-promoting electro-Fenton application process according to claim 5 3+ A method for preparing a reduced promoter, characterized in that: The microwave drying is carried out at 60-120° C. for 20-40 min.

8. The Fe-promoting electro-Fenton application process according to claim 1 3+ A method for preparing a reduced promoter, characterized in that: The power of S3 freeze drying is 500-1200W.

9. The Fe-promoting electro-Fenton application process according to claim 8 3+ A method for preparing a reduced promoter, characterized in that: The freeze drying described in S3 is carried out at -20 to -10°C for 10 to 30 minutes.

10. A Fe-enhanced electro-Fenton process according to any one of claims 1 to 9 3+ Preparation method of reduced co-catalyst obtained to promote Fe in electro-Fenton application process 3+ The reduced catalyst is a porous nano-spherical structure with a specific surface area of ​​1200-2500 g / cm 2 , porosity is 65%-85%, pore volume is 0.12-0.30g / cm 3 .

Citation Information

Patent Citations

  • RGO / MoS2 / Ce0.75Zr0.25O2 cathode material, and preparation method and application thereof

    CN110228838A

  • Preparation method and hydrogen evolution application of molybdenum disulfide flower-like nanospheres

    CN110339845A

  • Nano pompon-shaped molybdenum sulfide / wood-based carbon porous electrode material as well as preparation method and application thereof

    CN111905767A

  • Heterojunction type Fenton-like catalyst and preparation method thereof, and special system and method

    CN113663697A

  • Molybdenum disulfide / cobalt composite catalyst and preparation method and application thereof

    CN114540869A

Cited By

  • Electrocatalyst for electrochemically producing high-purity hydrogen peroxide as well as preparation and application of electrocatalyst

    CN121204733A

  • An electrocatalyst for the electrochemical production of high-purity hydrogen peroxide, its preparation and application

    CN121204733B